2017
DOI: 10.1152/ajplung.00416.2016
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of individualized lung recruitment strategies at birth: an experimental study in preterm lambs

Abstract: Background: In translational animal studies both a sustained inflation (SI) and PEEP have been associated with better lung aeration at birth, but the role of each on lung injury is inconclusive. We aimed to determine the effect of different PEEP and SI strategies at birth on early development of lung injury pathways. Method: 70 antenatal-steroid exposed lambs (125d AE 1d) were instrumented during caesarean section. Lambs were randomly assigned to either 1) Positive Pressure Ventilation (PPV; n = 20) using volu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
96
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(97 citation statements)
references
References 42 publications
1
96
0
Order By: Relevance
“…Increasingly, clinicians are using individualized ventilation strategies, such as open-lung ventilation and volume-targeting, in an effort to avoid harmful lung volume states and achieve regional homogeneity (7,32). Previous work from our group, limited to a single GA, demonstrated great heterogeneity in the time constants of the respiratory system at birth, which influenced SI aeration outcomes (2,14,16). We have now demonstrated that GA independently influences aeration during an SI.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…Increasingly, clinicians are using individualized ventilation strategies, such as open-lung ventilation and volume-targeting, in an effort to avoid harmful lung volume states and achieve regional homogeneity (7,32). Previous work from our group, limited to a single GA, demonstrated great heterogeneity in the time constants of the respiratory system at birth, which influenced SI aeration outcomes (2,14,16). We have now demonstrated that GA independently influences aeration during an SI.…”
Section: Discussionmentioning
confidence: 57%
“…Recent advances in electrical impedance tomography (EIT) have enabled monitoring of the aeration response of the lung from birth, allowing individual titration of the SI duration to the aeration response experimentally, with improved gas exchange and lung mechanics compared with a fixed 30-s SI (2,16). Although this approach offers more favorable lung aeration, it is currently a research tool only.…”
mentioning
confidence: 99%
“…The vectorial transport of NaCl generates an osmotic gradient, which contributes to fetal lung fluid formation, which fills the bronchial and alveolar spaces. Shortly before birth, Cl Ϫ secretion ceases, and Na ϩ absorption is initiated through the upregulated amiloride-sensitive ENaCs (68,78,101) (Fig. 1).…”
mentioning
confidence: 99%
“…However, studies in the premature lamb have shown better oxygenation, lung mechanics, and end-expiratory global lung volume after a dynamic PEEP strategy based on a step-by-step PEEP increase far beyond 5 cmH2O compared with a nonoptimized SI strategy [4,6]. However, none of these differences were observed when the dynamic PEEP strategy was compared with a SI strategy optimized by real time electrical impedance tomography for the duration of the inflation [5]. We hypothesized that individualized LR maneuvers combining dynamic PEEP and gradually extended SI, as needed, would lower the incidence of mechanical ventilation (MV) in the first 72 h, without increasing neonatal complications.…”
Section: Introductionmentioning
confidence: 97%
“…Resuscitating premature infants at birth aims to stimulate spontaneous breathing and establish an optimal functional residual capacity without harming the lungs [1]. To this end, lung recruitment maneuvers have been under investigation over the past two decades [2][3][4][5][6]. To date, despite numerous studies, no clear definition of the optimal inflation duration, nor of positive end-expiratory pressure (PEEP) optimal level exists.…”
Section: Introductionmentioning
confidence: 99%